Determination of Mechanical Properties of Walls Produced with Different Wall and Mortar Materials - Hanifi Tokgöz; Behcet Dündar (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2024)
Walls produced using different masonry materials and mortars are among the structural elements that carry horizontal and vertical loads. In this context, the mechanical properties of walls produced with different wall and mortar materials have been investigated. In the production of wall samples, Harman Brick (HB), Masonry Brick (MB) and Bimsblok (BB) were chosen as the mesh material Reinforced Mortar (RM) and Polypropylene Fiber Added Mortar (PM) were used as binding materials in the construction of the walls produced in 900x900 mm dimensions. The volumetric mixing ratios of the mortar used were prepared as sand:cement:lime=6:1:1, according to the TSE 2510 standard. The bricked wall samples were subjected to diagonal loading tests after being kept in the laboratory environment for 28 days. Flexural and compressive strengths of the mortars used in wall building, displacement values of the walls, shear strength, rigidity modulus, energy absorption capacity and collapse patterns of the walls were determined. The graphs of the displacement values obtained by examining the behaviors observed in the test samples and the cracks formed were interpreted. It was observed that the shear strength of the walls built using PM was higher than the shear strength of the walls built using RM. The energy absorption capacity was highest in the fibrous specimen laid with masonry bricks. The average vertical load value of the wall specimens built with fibrous mortar, which is the BB of the masonry material, was 30% higher than the specimens built with non-fiber mortar.